2008
DOI: 10.1097/ss.0b013e31816408ae
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Swine Effluent Application on Selected Soil Properties

Abstract: Improving swine effluent management practices requires understanding of the fate of nutrients derived from swine effluent in soil quality. This study was conducted to evaluate the effects of long-term swine lagoon effluent application on nutrient distribution in an alkaline Okolona silty clay, an acidic Vaiden silty clay, and a Brooksville silty clay loam. Swine effluent has been applied using a center-pivot irrigation system at a total rate ranging from 10 to 15 cm ha j1 of effluent per year since 1990. In Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 48 publications
4
33
2
7
Order By: Relevance
“…and 3.0, 0.15 and 2.6 % of the total applied through NPK, respectively. These low values of P transferred via surface runoff in the different nutrient sources are similar to the results obtained by Bertol et al (2010), who observed P transfer via surface runoff of less than 15 % of the total applied and suggested that the P remains accumulated in the soil surface layer, as verified in the present study (Table 2) and in other studies (Adeli et al, 2008;Scherer et al, 2010;Ceretta et al, 2010a;Guardini et al, 2012a). Nevertheless, after successive manure applications, there is a tendency for saturation of adsorption sites of the reactive particles of the soil.…”
Section: P Transfer Via Surface Runoffsupporting
confidence: 80%
See 2 more Smart Citations
“…and 3.0, 0.15 and 2.6 % of the total applied through NPK, respectively. These low values of P transferred via surface runoff in the different nutrient sources are similar to the results obtained by Bertol et al (2010), who observed P transfer via surface runoff of less than 15 % of the total applied and suggested that the P remains accumulated in the soil surface layer, as verified in the present study (Table 2) and in other studies (Adeli et al, 2008;Scherer et al, 2010;Ceretta et al, 2010a;Guardini et al, 2012a). Nevertheless, after successive manure applications, there is a tendency for saturation of adsorption sites of the reactive particles of the soil.…”
Section: P Transfer Via Surface Runoffsupporting
confidence: 80%
“…Considering the two crops, the transfer in the runoff solution was on average 49 % of the total rainfall volume in the treatment without nutrient application and 31, 25, 31 and 21 % of the total rainfall volume in the treatments with application of PS, PL, CS and NPK, respectively. This probably occurred because of the greater addition of organic matter in the treatments that received nutrient applications, be it through the concentration of dry matter in the residues added or through the greater production of dry matter of crop residues on the soil Adeli et al, 2008;Giacomini & Aita, 2008), which leads to an increase in the organic carbon contents in the soil (Lourenzi et al, 2011) and, consequently, improves the capacity of water infiltration in the profile, reducing the transfer of solution via surface runoff (Ceretta et al, 2010b).…”
Section: P Transfer Via Surface Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…A maioria dos trabalhos encontrados na literatura abordam os efeitos do uso de dejetos de suĂ­nos in natura, sem nenhum tipo de processamento, sobre os atributos quĂ­micos do solo (Adeli et al, 2008;Scherer et al, 2010;Brunetto et al, 2012). Portanto, Ă© importante avaliar os efeitos do uso de composto orgĂąnico produzido com dejetos de suĂ­nos sobre os atributos quĂ­micos do solo, uma vez que as caracterĂ­sticas desses resĂ­duos sĂŁo diferentes das dos dejetos lĂ­quidos, sobretudo quanto Ă  carga orgĂąnica e Ă  forma como os nutrientes sĂŁo aplicados ao solo.…”
Section: Introductionunclassified
“…Therefore a small soil contact area is expected, with a consequent delay in the microbial biomass activity, which may stimulate total organic carbon (TOC) accumulation (Ceretta et al, 2003;Adeli et al, 2008;Lourenzi et al, 2011), particularly in the surface layers. However, increases in TOC contents are mainly associated to the manure composition, application frequency and amount (Falleiro et al, 2003;Lourenzi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%